Changes in Cancer Patients' and Caregivers' Disease Perceptions While Receiving Early Palliative Care: A Qualitative and Quantitative Analysis. (29th September 2021) - Borelli, Eleonora; Bigi, Sarah; Potenza, Leonardo; Eliardo, Sonia; Artioli, Fabrizio; Mucciarini, Claudia; Cottafavi, Luca; Cagossi, Katia; Razzini, Giorgia; Cruciani, Massimiliano; Pietramaggiori, Alessandra; Fantuzzi, Valeria; et al.
Abstract : Background: Little is known about the underlying mechanisms through which early palliative care (EPC) improves multiple outcomes in patients with cancer and their caregivers. The aim of this study was to qualitatively and quantitatively analyze patients' and caregivers' thoughts and emotional and cognitive perceptions about the disease prior to and during the EPC intervention, and in the end of life, following the exposure to EPC. Materials and Methods: Seventy-seven patients with advanced cancer and 48 caregivers from two cancer centers participated in semistructured interviews. Their reports were qualitatively and quantitatively analyzed by the means of the grounded theory and a text-analysis program. Results: Participants reported their past as overwhelmed by unmanaged symptoms, with detrimental physical and psychosocial consequences. The EPC intervention allowed a prompt resolution of symptoms and of their consequences and empowerment, an appreciation of its multidimensional approach, its focus on the person and its environment, and the need for EPC for oncologic populations. Patients reported that conversations with the EPC team increased their acceptance of end of life and their expectation of a painless future. Quantitative analysis revealed higher use of Negative Affects ( p  < .001) and Biological Processes words ( p  < .001) when discussing the past; Agency words when discussing the present ( p  < .001); Positive Affects ( p  < .001), Optimism ( p  = .002), and Insight Thinking words ( p  < .001) when discussing the present and the future; and Anxiety ( p  = .002) and Sadness words ( p  = .003) when discussing the future. Conclusion: Overall, participants perceived EPC to be beneficial. Our findings suggest that emotional and cognitive processes centered on communication underlie the benefits experienced by participants on EPC. Implications for Practice: By qualitative and quantitative analyses of the emotional and cognitive perceptions of cancer patients and their caregivers about their experiences before and during EPC interventions, this study may help physicians/nurses to focus on the disease perception by patients/caregivers and the benefits of EPC, as a standard practice. The analysis of words used by patients/caregivers provides a proxy for their psychological condition and support in tailoring an EPC intervention, based on individual needs. This study highlights that the relationship of the triad EPC team/patients/caregivers may rise as a therapeutic tool, allowing increasing awareness and progressive acceptance of the idea of death. Abstract : Early palliative care can improve experiences and outcomes for patients with advanced cancer. This article analyzes disease perceptions of cancer patients and their caregivers before and after early palliative care intervention.